Legal principles and judicial decisions on environments in Malaysia: An overview - Md Dahlan, Nuarrual Hilal; Kamaruddin, Abdul Rani (2004)
The awareness that healthy environment is a necessity of human life, is increasing today. Long time ago, people only tended to lay emphasize on the satisfaction of their basic and personal human right, which would include foods, lodging, raiment as well as other simple constitutional rights such as freedom of speech etc.But now it evinces that, environmental safety and health right, though at the first glance and at the outset, seems only a peripheral right, it has become overwhelming and expedient to human life, that should be reckoned with.In respect of the law, it is manifestly clear that it could lend its aids protecting mankind against any adverse environmental wrongdoings.These would include providing legal remedies such as injunctions, damages, compensation or even imposition of criminal penalties against the defendants/perpetrators. Hence, this article will look into the law in Malaysia in regard to its ability to provide environmental protection based on the decided cases in courts.